2020
DOI: 10.1051/e3sconf/202020003013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Alfalfa (Medicago sativa L.) on different basal feeds for hybrid duck performance

Abstract: The aimed of this research was to determine effect of Supplementation of Alfalfa (Medicago sativa L.) on different basal feeds for hybrid duck performance. This research was conducted by in vivo method with 120 MA (Mojosari x Alabio) of hybrid ducks type. The method was being used in this research include 4 treatments and 6 repetitions with 5 ducks each repetition. The treatment consisteds of P1 = Commercial feed 100 %, P2 = Alternative feed 100 %, P3 = Commercial Feed 90 % + supplementation of fresh alfalfa 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…In this study, it was observed that there was no statistically significant difference in the FCR between treatments. These results are in close agreement with Samur et al ( 2020 ), who reported that the consumption of a diet contaminated with 200 ng AFB 1 /g feed does not show a significant difference in FCR in turkeys. Finally, the mortality observed during the experiment (7%) was not related to the dietary AFB 1 level, but rather due to yolk sac infection.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, it was observed that there was no statistically significant difference in the FCR between treatments. These results are in close agreement with Samur et al ( 2020 ), who reported that the consumption of a diet contaminated with 200 ng AFB 1 /g feed does not show a significant difference in FCR in turkeys. Finally, the mortality observed during the experiment (7%) was not related to the dietary AFB 1 level, but rather due to yolk sac infection.…”
Section: Resultssupporting
confidence: 92%
“…However, the three experimental groups that were fed with the diet contaminated with AFB 1 (AF, AF+alfalfa, and AF+YCW), showed a significant reduction in BWG compared to the Control and Alfalfa groups. These results are similar to those reported by Samur et al ( 2020 ), who showed that the supplementation of a commercial duckling diet with 10% (w/w) fresh alfalfa had no effect in BWG. Interestingly, poults that were given the diet supplemented with powdered alfalfa leaves had the greatest numerical value in BWG compared to the Control group (but not statistically significant).…”
Section: Resultssupporting
confidence: 92%
“…The above results may be related to the regulation of lipids from nutrients in alfalfa. Alfalfa contains a large amount of dietary fiber, which helps to reduce the cholesterol level in animals [ 50 , 51 ]. In addition, saponin, which is one of the main components of secondary metabolites in alfalfa, can also reduce the cholesterol level and LDL and inhibit the activity of cholesterol-related synthase [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, alfalfa contains large quantities of dietary fiber, which could help to lower cholesterol levels. The use of tropical alfalfa (Kacang Ratu BW) in ducks (35 days) from 3% up to a level of 10 % did not affect the production performance of ducks, but reduced FCR ( Suwignyo et al, 2020a , Suwignyo et al, 2020b , Suwignyo et al, 2020c , Suwignyo et al, 2020d , Suwignyo et al, 2021c , Suwignyo et al, 2021d ) reduced cholesterol from 66.5 to 34.8 mg/100 g ( Samur et al, 2020 ) from 177.7 to 116.2 mg/100g (in the liver), 162.9 to 134 mg/100 (in the blood) and reduced LDL from 83.70 to 68.0 mg/dL but increased HDL from 54.6 to 71.96 mg/dL ( Suwignyo et al, 2022 ). The use of 2 % tropical alfalfa in laying hens (hyline 50 weeks old) produced eggs with higher levels of Fe, Zn, beta carotene, vitamin A and antioxidants than controls, respectively 5.6 vs 4.9 mg/100 g, 3.4 vs 1 mg/100 g, 1818.1 vs 1512.7 µg/100 g, 4934.9 vs 4382.9 µg/100 g, 4.9 vs 15.8 %, making it good for nutritional intervention for stunting eradication programs, that are still high in several developing countries, including Indonesia ( Suwignyo and Indartono, 2022 ).…”
Section: Alfalfa As Food and Foragementioning
confidence: 99%
“…Higher income was generated from the ducks (live and carcass) supplemented exclusively with 6 % alfalfa, followed by those supplemented with both 6 % fresh alfalfa and the control diet. The study by Samur et al(2020) on the supplementation with alfalfa in different basal rations showed that by supplementing commercial and alternative feeds with 10 % fresh alfalfa had a significant impact on feed consumption, BW, and FCR. The commercial feed supplemented with 10 % alfalfa resulted in the highest feed consumption, BW, and FCR.…”
Section: The Nutrient Content Of Alfalfamentioning
confidence: 99%